2018
DOI: 10.1016/j.syapm.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota composition, gene pool and its expression in Gir cattle (Bos indicus) rumen under different forage diets using metagenomic and metatranscriptomic approaches

Abstract: Zebu (Bos indicus) is a domestic cattle species originating from the Indian subcontinent and now widely domesticated on several continents. In this study, we were particularly interested in understanding the functionally active rumen microbiota of an important Zebu breed, the Gir, under different dietary regimes. Metagenomic and metatranscriptomic data were compared at various taxonomic levels to elucidate the differential microbial population and its functional dynamics in Gir cattle rumen under different rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 75 publications
6
15
0
Order By: Relevance
“…Change in relative abundance of most of the methanogens or genes involved in CH 4 production did not seem important to explain differences between HME and LME. Similar results were previously shown in cattle and sheep (Béra-Maillet et al, 2004;Pandit et al, 2018) and also showed a lack of co-abundances between methanogenic populations, genes and CH 4 emissions (Zhou et al, 2011;Danielsson et al, 2012;Shi et al, 2014;Wallace et al, 2014;Tapio et al, 2017;Zheng et al, 2018). One explanation for this is the identification of different clades of Methanobrevibacter known to differ in their production of CH 4 (Tapio et al, 2017).…”
Section: Importance Of Methanogens Explaining Differences In Ch 4 Emisupporting
confidence: 87%
See 1 more Smart Citation
“…Change in relative abundance of most of the methanogens or genes involved in CH 4 production did not seem important to explain differences between HME and LME. Similar results were previously shown in cattle and sheep (Béra-Maillet et al, 2004;Pandit et al, 2018) and also showed a lack of co-abundances between methanogenic populations, genes and CH 4 emissions (Zhou et al, 2011;Danielsson et al, 2012;Shi et al, 2014;Wallace et al, 2014;Tapio et al, 2017;Zheng et al, 2018). One explanation for this is the identification of different clades of Methanobrevibacter known to differ in their production of CH 4 (Tapio et al, 2017).…”
Section: Importance Of Methanogens Explaining Differences In Ch 4 Emisupporting
confidence: 87%
“…Interestingly, Candidatus Azobacteroides carrying in its genome the nitrifying gene K02588 had both a strong and positive relationship with CH 4 emissions. Moreover, this genus was shown to be highly active by metatranscriptomics in the rumen of Bos indicus across different dietary treatments confirming its importance in the rumen microbiome (Pandit et al, 2018). Such new result confirmed the FIGURE 3 | Focus on the "methanogenesis" cluster in co-abundance networks (correlation threshold of 0.70) in (A) high (HME) and (B) low (LME) methane emitters of beef cattle.…”
Section: Importance Of Methanogens Explaining Differences In Ch 4 Emisupporting
confidence: 66%
“…most similar to C. kristjanssonii based on 16S rDNA analysis were identified from manure-supplemented distillery waste streams [57], although it is unclear if the Caldicellulosiruptor cells came from the distillery wastewater or the digested cow manure. Additional reports of Caldicellulosiruptor species identified from animal microbiota included community analyses of a rumen microbial community [58], and poultry caecum community [59] opening up the exciting prospect of mesophilic relatives of the Caldicellulosiruptor ("Mesocellulosiruptor"), similar to the discovery of mesophilic members of the phylum Thermotogae (reviewed in [60]). Caldicellulosiruptor species were also detected in the latter stages of a human waste-amended thermophilic aerobic digestor in Japan [61], and by community analysis from anaerobic digesters present in France [62], India [63], China [64], and Hungary [65].…”
Section: Caldicellulosiruptor Community Analysesmentioning
confidence: 99%
“…Here, we present 1200 high-quality metagenomic assembled genomes from the rumen of African Zebu exposed to a restricted feeding regime representing the food-scarce circumstances faced by many smallholder farmers in sub-Saharan Africa. Although not a direct estimation of abundance, the distribution of MAGs classified in each of the major rumen phyla, Bacteroidetes (29.76%), Firmicutes (44.35%) and Proteobacteria (7.65%), is comparable to the abundance of these phyla in other cattle rumen communities [ 23 ] and those of indicine or cross breed cattle origin, whether using a 16S amplicon sequencing approach [ 8 , 24 , 25 ] or metagenomic read classification [ 26 ]. The proportion of MAGs classified to each of the major rumen phyla is also comparable to those recovered from Scottish cattle [ 11 ].…”
Section: Discussionmentioning
confidence: 99%